Sustainable Tourism Development Index: A Scientifically Practical Proposal - Diakomihalis, Mihail N; Diakomichalis, Nikolaos-Marios (Environmental Management and Sustainable Development, 2023)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Sustainable tourism development requires self-limitation and the delimitation on national or regional development, within the frame of Carrying Capacity (CC), while maximizing economic benefits evaluated in the Tourist Satellite Account (TSA). <em style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Sustainable Tourism<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;"> should be determined by Carrying Capacity while <em style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Development <span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">level should be depicted on Tourism Satellite Account, at national or at local level. The research question of this study is to define where the “golden ratio” is located between sustainability and economic benefits maximization. Tourism experts and academics evaluated the sub-criteria, based on the Analytic Hierarchy Process (AHP), which form the Sustainable Tourism Index, within the framework of environmental protection, natural sources savings, eco-friendly practices, green investments, and of the highest contribution to GDP, to employment, to local income and to local and federal tax revenues. The results will support local and federal policy makers to design and apply tourism development ensuring sustainability.